Chemical composition of feed resources in Bihar - DEY, A; BARARI, S K; BHATT, B P (The Indian Journal of Animal Sciences, 2014)
Feeding system of livestock depends on the availability of crop residues and by-products and pasture and grasses on common property resources. The present work was, therefore, taken up to assess the proximate compositions of commonly available feed stuffs in Bihar. Feed samples were collected from 40 households of 4 villages of north Bihar and 40 households of four villages of south Bihar. The average DM content of cereal crop as well as the leguminous crop residues varied between 89 and 93%. The chemical compositions of cereal crop residues revealed that the CP content was very low varied between 2.9 and 3.4% while fibre content was very high and varied between 32 and 37%. The CP content in grain and pulses used for feeding of livestock varied from 8 to 18% with highest value in gram flour. The wheat and rice bran and pulses chunies constitute the larger part of the dairy ration. The chemical composition of pulses chunies and bran depicts that they contained 14 to 15 and 10 to 14% CP, respectively. Horticulture waste contains 5 to 19% CP and 2 to 4% EE. Three types of oil-cakes are used for feeding livestock. All over the state, mustard cake is used as primary source of protein. Linseed-cake is only used for feeding dairy cow and buffalo. The chemical compositions revealed that the oil-cakes contained 31 to 33% protein and 3 to 8% EE. The present study revealed that available fodder resources had good nutritional values. However, energy values and mineral contents of feed resources have to be worked out for better understanding ofnutrients intake.